Answer:
(3, 0)
Explanation:
So with the 2 equations you can either choose which to start with but you need to make the X or Y the opposite from the other equation.
1.
3x + y = 9 (keep as is)
x + 2y = 3 --> -3( x + 2y = 3) In this case I chose to make the X the opposite of each other
--
3x - 3x = 0 (forced to get rid of)
y - 6y = -5y (Get the -6 by -3 x 2)
9 - 9 (Get the -9 by -3 x 3)
Left with:
-5y = 0 (Divide both sides by -5 to get X alone)
y = 0
----------------------------------------------------------
(Choose any ORIGINAL equation)
x + 2y = 3
x + 2(0) = 3 (substitute)
Left with:
x = 3 (x + 0 = 3)
-------------------------------------------------------------
Optional:
Chose the other equation (the opposite from above)
Substitute X and Y in 3x + y = 9
3(3) + (0) = 9
Left with: 9 = 9 (check)
Hope this helps!